Preferensi Konsumen terhadap Tingkat Kepentingan Atribut Beras dan Konsumsi Beras Rumah Tangga dengan Pendapatan yang Berbeda di Kota Palembang - Yunita, Yunita; Lifianthi, Lifianthi; Arbi, M. (Seminar Nasional Lahan Suboptimal, 2019)
Yunita Y, Lifianthi L, Arbi M. 2019. Consumer preference for the level of importance of rice atributes and household rice consumption with different income in Palembang City. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 459-467. Palembang: Unsri Press.Â Analysis of consumer preferences for rice and the household rice consumption and the factors that influence it are very important to learn, because it can be one of the bases for developing rice product development strategies. The objectives of this research are: 1) Analyzing consumer preferences for the importance of rice attributes, 2) Analyzing the household rice consumption, and 3) Analyzing the factors that influence the demand for household rice consumption. This research was conducted in June 2019 in Palembang. The research design was descriptive analytical with the survey method. This study also provided questionnaires to respondents sampled. Sampling is done through the area sampling techniques, taking into account sub-districts based on income strata used stratified random sampling. This research used 100 respondents consisted of 50 low income households and 50 high income households. The first goal is answered by using a scoring analysis with a Likert Scale, the second goal is answered using mathematical calculations, and the third goal is analyzed using multiple linear regression. The results showed that: 1) Most low-income household consumers consider that the attributes of rice which include durability/storage of rice, the color of rice/degree of white, rice dryness, taste of rice and brand of rice are important attributes and are very important to consider in choosing rice to be consumed. While high-income household consumers mostly prefer the attributes of rice extinction, flavor of rice, durability/storage of rice, type of rice and rice brands categorized into important and very important factor 2) The average demand for low-income household rice was 19, 24 kg/month, whereas high income households at 16.36 kg/month, 3) Low income household rice demand was influenced by gender and number of household members, while high income households was influenced by age and number of household members.Keywords: attributes of rice, household rice consumption, income, consumer preferences